2005
DOI: 10.1145/1047671.1047677
|View full text |Cite
|
Sign up to set email alerts
|

The state of user-centered design practice

Abstract: User-Centered Design (UCD) is a multidisciplinary design approach based on the active involvement of users to improve the understanding of user and task requirements, and the iteration of design and evaluation. It is widely considered the key to product usefulness and usability---an effective approach to overcoming the limitations of traditional system-centered design. Much has been written in the research literature about UCD. As further proof of internationally endorsed best practice, UCD processes are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
166
0
23

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(212 citation statements)
references
References 4 publications
1
166
0
23
Order By: Relevance
“…Keen and Scott Morton [48] emphasized in several contexts that a DSS must be tailored to match the decision maker (user) (pp. 6,11,50,58). This matching was supported by a highly iterative development process, including both prototyping and evolutionary development [48], which are used to characterize also UCD (e.g.…”
Section: User-centeredness As User Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…Keen and Scott Morton [48] emphasized in several contexts that a DSS must be tailored to match the decision maker (user) (pp. 6,11,50,58). This matching was supported by a highly iterative development process, including both prototyping and evolutionary development [48], which are used to characterize also UCD (e.g.…”
Section: User-centeredness As User Focusmentioning
confidence: 99%
“…1 However, despite the interest [58], the concept is still unclear [11], [29], [45], [54]. Although the phrase "user-centered" emerged in the human computer interaction (HCI) field, it can be argued of having adopted ideas from different sources, such as prototyping [48], [23], [10], evolutionary delivery [48], socio-technical design [6], [64], [72], [21], user participation [64], participatory design [27], [77] and usability engineering (UE) [45], [63], [66].…”
Section: Introductionmentioning
confidence: 99%
“…This section begins with a review of user-centered design methods all of which are meant to discover what the user needs, wants, and is capable of using (Rosenbaum, Rohn, & Humburg, 2000;Mao et al, 2005, Vredenburg et al, 2002. The methods range from large scale data gathering, like surveys, to intimate, face-to-face interactions.…”
Section: Methods Of User-centered Designmentioning
confidence: 99%
“…Of those practicing UCD, one investigation revealed that the majority of methods in practice were informal, low-cost user-centered design methods. The most commonly used methods were iterative design, usability evaluation, task analysis, informal expert review, and field studies [15]. Obstacles given for not implementing UCD techniques include a lack of awareness of usability across the company, lack of usability experience, poor management support and marketing pressures [16].…”
Section: Usability and Web Development Processesmentioning
confidence: 99%